2020
DOI: 10.1088/1755-1315/570/5/052012
|View full text |Cite
|
Sign up to set email alerts
|

Presplitting cutting slots technique of roof cutting entry retaining and its impact on strata behavior law of workface in Baoshan coal mine

Abstract: Presplitting cutting slots advance working face is the key technology of non—pillar gob—side entry retaining formed by roof cutting and pressure release. And the rationality of parameters not only affects the formation of the structural surface of joint-cutting, but also has a significant impact on the retaining roadway. In order to enrich and improve the system of presplitting cutting slots technology, this paper takes the 6302 working face in Baoshan Coal Mine as the research object to discuss the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…18,25 To summarize the research results, in terms of roof-cutting parameters, an applicable system can be identified for a certain selection of angle, height, hole spacing, and explosive structure. [26][27][28][29] Additionally, the new presplitting blasting method has achieved fruitful results. 30 In terms of support, studies on roof deformation mechanisms, 31 roof structure evolution characteristics, 32 roof control mechanisms, technology, and methods 33 have achieved fruitful results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,25 To summarize the research results, in terms of roof-cutting parameters, an applicable system can be identified for a certain selection of angle, height, hole spacing, and explosive structure. [26][27][28][29] Additionally, the new presplitting blasting method has achieved fruitful results. 30 In terms of support, studies on roof deformation mechanisms, 31 roof structure evolution characteristics, 32 roof control mechanisms, technology, and methods 33 have achieved fruitful results.…”
Section: Introductionmentioning
confidence: 99%
“…At present, GERRC has been successfully applied at shallow to deep depth, 19,20 for thin to medium coal seams 16,21,22 and thick coal seams, 23 in hard roofs to composite roofs, 17,24 and for highly dipping coal seams and broken roofs 18,25 . To summarize the research results, in terms of roof‐cutting parameters, an applicable system can be identified for a certain selection of angle, height, hole spacing, and explosive structure 26–29 . Additionally, the new presplitting blasting method has achieved fruitful results 30 .…”
Section: Introductionmentioning
confidence: 99%